Development of an ultra-sensitive electrochemical sensor for Δ9-tetrahydrocannabinol (THC) and its metabolites using carbon paper electrodes. (1st June 2019) - Renaud-Young, Margaret; Mayall, Robert M.; Salehi, Vajiheh; Goledzinowski, Maciej; Comeau, Felix J.E.; MacCallum, Justin L.; Birss, Viola I.
Abstract: With the legalization of recreational cannabis use, there is a need to develop a rapid and accurate roadside test that can be used to analyze human saliva samples for Δ 9 -tetrahydrocannabinol (THC), the main psychoactive ingredient in cannabis. Here we demonstrate a novel drug detection method where THC is infused into carbon paper electrodes followed by electrochemical detection in a pH 10 aqueous solution. This method produces a linear, sensitive (down to ∼ 1 pmol), dose-dependent change in the oxidation peak current that varies with THC surface densities. These results, as well as the peak charge per real carbon surface area and linear current/scan-rate dependence, support a model for the distribution of THC on the carbon surface in a thin-layer configuration, facilitating the oxidation of the deposited drug. We also demonstrate electro-oxidation of the two major metabolites of THC, the psychoactive 11-hydroxy-tetrahydrocannabinol (OH-THC), and the non-psychoactive 11-nor-9-carboxy-tetrahydrocannabinol (COOH-THC), that also produce linear, dose-dependent changes in peak charge. However, COOH-THC exhibits a much lower Faradaic efficiency than OH-THC and THC, suggesting that variations in the THC functional groups affect the electro-oxidation of the cannabinoids. Overall, this work illustrates a novel, reproducible, and sensitive method for the analysis of THC and oxidation properties of its common metabolites that could be adapted for use with human saliva samples in future work.